2018
DOI: 10.18632/genesandcancer.171
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplasia in pancreatic ductal adenocarcinoma: insight into pathological function and therapeutic potential

Abstract: Extensive desmoplasia is a prominent feature of the pancreatic ductal adenocarcinoma (PDAC) microenvironment. Initially, studies demonstrated that desmoplasia promotes proliferation, invasion and chemoresistance in PDAC cells. While these findings suggested the therapeutic potential of targeting desmoplasia in PDAC, more recent studies utilizing genetically-engineered mouse models of PDAC, which lack key components of desmoplasia, demonstrated accelerated progression of PDAC. This contrast calls into question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 48 publications
(73 reference statements)
2
70
0
Order By: Relevance
“…Further analysis showed that most of the proteins encoded by the identified up/ down-regulated genes are components of the extracellular matrix, which is in line with the fact that PDAC has a characteristically abundant desmoplastic stroma (Cannon et al, 2018). Moreover, the gene ontology analysis revealed that the identified up-regulated genes in PDAC generally encode extracellular matrix (ECM) structural elements together with the proteins with collagen and integrin-binding properties.…”
Section: Discussionsupporting
confidence: 60%
“…Further analysis showed that most of the proteins encoded by the identified up/ down-regulated genes are components of the extracellular matrix, which is in line with the fact that PDAC has a characteristically abundant desmoplastic stroma (Cannon et al, 2018). Moreover, the gene ontology analysis revealed that the identified up-regulated genes in PDAC generally encode extracellular matrix (ECM) structural elements together with the proteins with collagen and integrin-binding properties.…”
Section: Discussionsupporting
confidence: 60%
“…Strategies to ablate the culprit CAFs have indeed reduced stroma, yet offered no benefit to pancreatic ductal adenocarcinoma (PDAC) patients 55 , or in some cases even dangerously promoted cancer progression 56 , 57 . Thus, there is growing appreciation for “stroma normalization”, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2019). The inhibition of stroma-cancer cell interactions is currently attracting a lot of interest as a promising strategy that may sensitize PDAC to therapy and increase the 5-year survival rate of patients suffering from this disease (Cannon et al, 2018).…”
Section: Pscs In Diseases Of the Pancreasmentioning
confidence: 99%